The Role of Literature to Improve Reading Skill According to Students Preferences - Zulkarnain, Elva Nadia; Nur, Dedi Rahman ((JELE) Journal Of English Language and Education, 2021)
This article discusses the application of literature in the form of a reading text to improve language skills for students of language education. Here, using a direct method experiment by 10 students in which they will be free to choose literature in the form of reading text that they like or according to literary work that they like and also specified essay. for example, they like to read novel so they may use novel in this research. In this research, it was proven that if students learn what they like or hobbies that are in the form of literature it will make it easier for them to learn languages and they enjoy the learning process.Â